Let S be a nonempty bounded set in R.
a.) let a>0, and let aS := (as:s element S). prove that, inf (aS)= a inf S, and sup (aS)= a sup S
b.) let b<0, and let bS := (bs:s element S). prove that, inf (bS)= b sup S, and sup (bS)= b inf S.
1
Expert's answer
2011-09-18T17:51:15-0400
First we show that
(1)& sup(aS)= a sup(S)
(2)& inf(-S)= -sup(S).
and then deduce from these statement all others.
Proof of (1). By definition x = sup T if x>=t for any& t from T, and for any p>0 there exists& t'& from T such that t' > x-t
First we show that sup(aS) <= a sup(S) Indeed, since&
s <= sup(S) for all s from S, then & as <= a sup(S), whence & sup (aS) <= a sup(S),
To prove the converse inqeuality& sup(aS) >= a sup(S) suppose that& sup(aS) < a sup(S) Then there exists b such that (*) sup(aS) < ab < a sup(S) But this means that s < b for all s from S, and so sup(S) <= b. Hence & a sup(S) <= ab which contradicts to (*). Hence sup(aS) = a sup(S).
Proof of (2). Since & s <= sup(S) for all s from S, it follows that & -s >= -sup(S), whence
inf(-S)>=-sup(S).
Conversely, suppose that inf(-S) > -sup(S), so there exists x such that (**) inf(-S) > x > -sup(S).
Then the first part of this inequality inf(-S) > x implies that& -s > x for all s from S, so s < -x, whence sup(S)<= -x, and therefore -sup(S)>= x, which contradicts to (**).
================ Now we can prove that
(3)& inf(aS) = a inf(S).
Indeed: & inf(aS) = inf( - (-aS) )& = by (2) = = -sup(-aS) = -sup(a*(-S)) = by (1) = = - a * sup(-S) = by (2) = = a * inf(S)
Let b<0. Let us prove that (4) inf (bS)= b sup S (5) sup (bS)= b inf S
Proof of (4). Since -b>0 we obtain & inf(bS) = inf (-b * (-S) ) = by (3) = -b * inf(-S) = = by (2) = -b * (-sup(S)) = = b * sup(S).
Proof of (5). Again & sup(bS) = sup (-b * (-S) ) = by (1) = -b * sup(-S) = = by (4) = -b * inf(-S) = = by (2) = -b * (-sup(S)) = = b * sup(S)
Comments
Leave a comment